Posterior Corneal Asphericity Effect on Postoperative Astigmatism after EDOF Intraocular Lens Implantation in Cataract Patients - Mark Rabinovich; Ivo Guber; Laëtitia Jessy Niegowski; Ana Maria Aramburu del Boz; Danial Al Khatib; Jean-Pascal Genestier; Jerome Bovet (Journal of Ophthalmology)
Aim. To assess the impact of posterior corneal asphericity on postoperative astigmatism. Methods. We included retrospectively 70 eyes of 70 patients that underwent cataract surgery. We included data of the Q value, Kmax, K1, K2, astigmatism AL, and ACD. We performed a vectorial analysis to calculate the astigmatic vectors. Results. Seventy eyes were evaluated. 40 eyes were of females (58%) and 30 of males (42%). The average cohort age was 73 ± 8.9 years. Axial length (AL) was 23.5 ± 0.9, anterior chamber depth (ACD) was 3.13 ± 0.3, and the average posterior Q value was −0.35 ± 0.2. The only significant predictive variable for the correction index (CI) was the posterior Q value (r = 0.24, p < 0.05) and for the surgically induced astigmatism (SIA) (β = 0.34, r = 0.58, p < 0.05). Conclusion. Posterior corneal surface asphericity significantly influences the surgically induced astigmatism and the overcorrection for cataract patients after Lucidis EDOF IOL implantation.